Spatial impacts of economic crisis. Scenarios for the Portuguese Regions - Tomaz Dentinho; Jo\~ao Borba (European Regional Science Association (ERSA), 2014)
Unemployment and migration are known effects of financial and economic crisis. This paper tries to understand the spatial patterns of those effects in a city and its surroundings considering the direct and induced impacts, the migration flows between the city, the surroundings and the outside and the multiplier effects that come from the changing rents of the economic landscape. We use a spatial interaction model with rent calibration and the cyclical results of the distribution of rents and unemployment subsidies. We apply the model to Portuguese NUTS 3 regions where the reduction of some basic economic activities is producing direct and induced impacts on unemployment, reduction of active population and migration.
Keywords: R10; 330